Measuring household energy efficiency behaviors with attention to behavioral plasticity in the United States. (November 2015) - Allen, Summer; Dietz, Thomas; McCright, Aaron M.
Abstract: Household energy consumption remains ripe for behavioral intervention, being responsible for an estimated 31% of U.S. CO2 emissions. As researchers attempt to understand the factors that influence household energy efficiency behaviors, we suggest it is important to attend to behavioral plasticity—how the perceived difficulty of behavioral responses varies across individuals, behaviors, and contexts. We present a new instrument composed of behaviors identified in previous analyses as having the highest impact on residential energy consumption. Our instrument allows for the specific measurement of self-reported behaviors, behavioral intentions, and inability to perform behaviors. Results from a convenience sample of 1522 U.S. adults demonstrate the construct validity of this instrument, as key factors known to influence pro-environmental behaviors—e.g., key environmental beliefs and attitudes—predict household energy efficiency behaviors.